Penerapan Medıa Gambar Untuk Menıngkatkan Keterampılan Berbıcara Sıswa Di Kelas II SD Negerı Bagında 1 - Maemunah, Maemunah (Journal of Innovation in Primary Education, 2023)
This research was motivated by the low learning outcomes of students in speaking skills in class II of SD Negri Baginda 1. The aim of this research was to determine the improvement of speaking skills through image media in Class II of Elementary School Negeri Baginda 1, Sumedang District, Sumedang Regency. The subjects in this research were class II students at SDN Baginda 1, Sumedang District, Sumedang Regency, totaling 23 students. Data collection techniques use observation, interviews, tests, and documentation. The data analysis technique uses qualitative description. The results of the research show that: (1) The implementation of improving speaking skills using image media in class II of SDN Baginda, Sumedang District, Sumedang Regency has been proven to improve students' speaking skills, and (2) The use of image media in improving students' speaking skills in class II of SDN Baginda 1 Sumedang District, Sumedang Regency, has been proven to be able to improve students' speaking skills, this can be seen from the increase in the class average score from student test results at each stage of the cycle, namely, the class average score in the pre-cycle was 49.41, in the first cycle amounted to 61.68, and in cycle II amounted to 73.53.